(NnEOBYKNOWENNOE LETO(B: [(NrOMAN(B] /s (N~ASTX (B6s - (NfEDIN(B, (NkONSTANTINs ((NmOSKWA(B:s (NhUDOVESTWENNAQ LITERATURA(B,s, 1984)
(Nw TOM WKL@^ENA WTORAQ ^ASTX TRILOGII PISATELQ(B-(NROMAN (B"(NnEOBYKNOWENNOE LETO(B".s
rus
Keywords: (NkLASSI^ESKAQ PROZAs; (NfANTASTIKA(B, (NF\NTEZIs; (NrOMANs